Aromatase inhibitor treatment for breast cancer: short-term effect on bone health - Erbağ, Gökhan; Uygun, Kazım; Binnetoğlu, Emine; Korkmaz, Ayşe Nurdan; Aşık, Mehmet; Şen, Hacer; Güneş, Fahri; Eroğlu, Mustafa; Gökmen, Ferhat; Temiz, Süleyman (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of this study was to examine the effects of aromatase inhibitors (AIs), which are used in every phase of breast cancer treatment, on the bone mineral density (BMD) of patients with early-stage breast cancer. Material and methods: Menopausal female patients who were diagnosed with stages 1–3 breast cancer and who were planned for anastrazole or letrozole as adjuvant therapy were examined. After the patients’ BMD was measured, 45 patients without osteoporosis were included in the study. Six months after AI therapy started, the patients’ BMD was measured again. Results : In this study, we tried to show that there was a statistical difference in the BMD of 45 patients before and 6 months after treatment. Among all measurements (femur and lumbar T-scores), the femur Z-score (p = 0.52) was the only score that was not statistically significant. Statistical significance (p < 0.01) was detected in comparative analysis of the other measurements. According to this analysis, a significant loss of BMD was seen even in the first six months after AI treatment was introduced. Conclusions : Female patients with breast cancer are at higher risk for bone loss and fractures than healthy women. In this study, we showed the negative effects on BMD of aromatase inhibitor therapy, one of the main contributions to osteoporosis in women with breast cancer. This study is the first to quantify the short-term effect of AI treatment on BMD in postmenopausal women with breast cancer.